Exploring Legal and Non-legal Approaches to Eliminating Child Labor in the Cocoa Industry in Ghana - Ansong, Alex; Agomor, Kingsley S. (Journal of Legal Studies, 2024)
The problem of child labor in cocoa-producing countries like Ghana and Ivory Coast has been projected into the international limelight due to coverage by notable international media organizations like CNN, BBC, and Al Jazeera. The incidence of child labor in the cocoa industry raises legal and ethical issues in the production and manufacturing processes that feed into international trade. This paper explores the international legal framework on child labor under the Minimum Age Convention and the consistency of Ghanaian domestic law with the Convention. It further discusses empirical data collected from Anyinam, a cocoa farming community in the Eastern Region of Ghana and the sustainability programme of Federated Commodities Ltd. (FEDCO), as a private sector responsible business initiative aimed at addressing the problem of child labor from a holistic approach.